Carlos E. Restrepo y el republicanismo de 1910. A los 101 años de la reforma constitucional, polémicas y debates políticos (2011)
ABSTRACT: The last year the Constitutional Reform of 1910 was 100 years, that fact is decisive to historic bases of rule of law in Colombia. That reform is pillar of our legal system, wich wasn’t studied by the academy. The next essay rebuilds the politic and legal effects of the Republicanism Project suggested by the president Carlos E. Restrepo (1910-1914). This article explores, the historic context, the politic impact, and the social processes that supported the republican proposal in the XX century in our country. The article shows the principals precedents, development and the definitions of politic project known how of the Republicanism, the problems, for example the dilemmas that such had, confilcts, polemics, contradictions between elites, the one thousand days war (1899- 1902) and the consequences that had of the five years of Reyes goverment.